2008
DOI: 10.1289/ehp.10742
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Organogenesis by the Herbicide Atrazine in the AmphibianXenopus laevis

Abstract: BackgroundExposure to anthropogenic chemicals during development can disrupt the morphogenesis of organ systems. Use of the herbicide atrazine has been debated in recent years because of its implicated, but poorly characterized, effects on vertebrates. Previous studies primarily examined the effects of atrazine exposure during metamorphosis or early developmental stages of amphibians.ObjectivesWe sought to identify and characterize the susceptibility during the often-overlooked developmental stage of organ mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 64 publications
(98 reference statements)
4
35
0
12
Order By: Relevance
“…Even after tadpoles of four different amphibian species begin feeding, there is a differential response to low atrazine concentrations such that early or late larval stages appear to be more sensitive to atrazine exposure depending on the species (Storrs and Kiesecker, 2004). Previously, we also showed that acute atrazine exposure just prior to the onset of feeding disrupts proper development of the anterior-posterior axis, heart, intestines, kidney and midbrain of X. laevis tadpoles (Lenkowski et al, 2008). Interestingly, other vertebrates examined have shown increased sensitivity to atrazine during organ morphogenesis, suggesting it may be a particularly sensitive developmental stage across vertebrates.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Even after tadpoles of four different amphibian species begin feeding, there is a differential response to low atrazine concentrations such that early or late larval stages appear to be more sensitive to atrazine exposure depending on the species (Storrs and Kiesecker, 2004). Previously, we also showed that acute atrazine exposure just prior to the onset of feeding disrupts proper development of the anterior-posterior axis, heart, intestines, kidney and midbrain of X. laevis tadpoles (Lenkowski et al, 2008). Interestingly, other vertebrates examined have shown increased sensitivity to atrazine during organ morphogenesis, suggesting it may be a particularly sensitive developmental stage across vertebrates.…”
Section: Introductionmentioning
confidence: 74%
“…Adult Xenopus laevis (Nasco, Fort Atkinson, WI, USA) were housed and eggs were collected as previously described (Lenkowski et al, 2008). Embryos were reared in 0.1¥ Marc's modified Ringer's solution (MMR; 0.01 M NaCl, 0.2 mM KCl, 0.1 mM MgCl2, 0.2 mM CaCl2, 0.5 mM HEPES; pH 7.5, Fisher Scientific).…”
Section: Animal Husbandrymentioning
confidence: 99%
See 2 more Smart Citations
“…‫البرمائيات‬ ‫ودعاميص‬ ‫الجنة‬ ‫التطورية‬ ( 1 ) ‫تشوه‬ ‫يسبب‬ ‫لالترازين‬ ‫البرمائيات‬ ‫اجنة‬ ‫تعرض‬ ‫بان‬ ‫الدراسات‬ ‫احدى‬ ‫اشارت‬ ‫اذ‬ ‫الهضمية‬ ‫االنظمة‬ ‫في‬ ‫وخلل‬ ‫كلوي‬ ‫وضعف‬ ‫قلبي‬ ( 2 ) ‫للقلب‬ ‫البطيني‬ ‫االذيني‬ ‫الصمام‬ ‫تشوه‬ ‫الى‬ ‫ادى‬ ‫اخرى‬ ‫دراسات‬ ‫وفي‬ ( 3 ) ‫كما‬ ‫التفافها‬ ‫وعكس‬ ‫االمعاء‬ ‫طول‬ ‫زيادة‬ ‫الى‬ ‫ادى‬ ( 4 ) ‫الدعاميص‬ ‫ذيول‬ ‫تقوس‬ ‫ويسبب‬ ( 5 ) . ‫به‬ ‫الملوثة‬ ‫المياه‬ ‫شرب‬ ‫عند‬ ‫الرضع‬ ‫االطفال‬ ‫اوزان‬ ‫انخفاض‬ ‫الى‬ ‫يؤدي‬ ‫كما‬ ( 6 ) ‫مما‬ ‫التعظم‬ ‫في‬ ‫نقص‬ ‫العالية‬ ‫الجرعات‬ ‫وتسبب‬ ‫االرانب‬ ‫اجنة‬ ‫في‬ ‫الوزن‬ ‫نقص‬ ‫يسبب‬ ( 7 ) ‫وتاخر‬ ‫ناضجة‬ ‫وغير‬ ‫الوزن‬ ‫منخفضة‬ ‫اجنة‬ ‫والدة‬ ‫في‬ ‫المبيد‬ ‫تاثير‬ ‫اكدت‬ ‫اخرى‬ ‫ودراسة‬ ‫عيو‬ ‫عن‬ ‫فضال‬ ‫الجنسي‬ ‫والنضج‬ ‫العظام‬ ‫تطور‬ ‫به‬ ‫الشرب‬ ‫مياه‬ ‫تلوث‬ ‫عند‬ ‫والدية‬ ‫ب‬ ( 8 ) ‫االجنة‬ ‫اجهاض‬ ‫حاالت‬ ‫من‬ ‫ويزيد‬ ( 9 ) ‫المشيمة‬ ‫على‬ ‫تاثيره‬ ‫خالل‬ ‫من‬ ‫لالجنة‬ ‫منخفضة‬ ‫بقاء‬ ‫نسبة‬ ‫ويسبب‬ ( 10 ) ‫االناث‬ ‫في‬ ‫حيضية‬ ‫مشاكل‬ ‫الى‬ ‫ويؤدي‬ ( 11 ) ‫ايضا‬ ‫ويسبب‬ ‫الرحم‬ ‫جدار‬ ‫سمك‬ ‫في‬ ‫زيادة‬ ( 12 ) ‫الجني‬ ‫للتطور‬ ‫االولى‬ ‫المراحل‬ ‫في‬ ‫الجرذان‬ ‫اجنة‬ ‫وتعرض‬ ‫في‬ ‫الثديية‬ ‫الغدد‬ ‫نمو‬ ‫تاخر‬ ‫يسبب‬ ‫ني‬ ‫االناث‬ ( 13 ) ‫االستروجين‬ ‫هرمون‬ ‫مستوى‬ ‫وزيادة‬ ( 14 ) ‫للحيامن‬ ‫الحركية‬ ‫القدرة‬ ‫ويخفض‬ ( 15 ) ‫الحيامن‬ ‫عدد‬ ‫انخفاض‬ ‫يسبب‬ ‫كما‬ ‫الذكور‬ ‫في‬ ( 16 ) ‫الذكور‬ ‫في‬ ‫المناعية‬ ‫االستجابة‬ ‫ويثبط‬ ( 17 ) ‫الوراثي‬ ‫والضرر‬ ‫لالترازين‬ ‫التعرض‬ ‫ارتباط‬ ‫اخرى‬ ‫دراسة‬ ‫وبينت‬ ‫الكروموسومات‬ ‫تلف‬ ‫زيادة‬ ‫الى‬ ‫يؤدي‬ ‫كما‬ ‫الفقريات‬ ‫في‬ ( 18 ) .…”
Section: ‫في‬ ‫درس‬ ‫االترازين‬ ‫االعشاب‬ ‫مبيد‬ ‫استعمال‬ ‫تكوينهااunclassified